Economic Regionalization and Black Sea in a Comparative Perspective - (:unkn) unknown (My University, 2017)
Soğuk Savaşın bitişinden bu yana bölgelerin çalışılması siyaset bilimi çalışmaları içerisinde öncelikli bir alan haline gelmeye başladı. Fakat hala bölgeselcilik birçok kişi için bir sürü farklı bağlamda oldukça farklı anlamlara geliyor. Yine de ekonomik karşılıklı bağımlılık ve bölge içi artan ticaret herhangi bir bölgeselcilik örneği için olmazsa olmaz koşullardan bir tanesi. Bu çalışmanın temel hareket noktası da bölgeselcilik ve ekonomik aktivitenin bölgeselleşmesi arasında teoride kurulan bu bağdır. Bu bağlamda, Karadeniz'de bölgeseliciliğe ya da bölgeselleşmeye bakmanın bir yöntemi ekonomik aktivitenin bölgeselleşmesinin incelenmesi olacaktır. Bu çalışmanın amacı da ticaret ve ekonomik aktivite verileri üzerinden Karadeniz bölgesini, muhtemel alt bölgeleri diğer bölgeselcilik örnekleri ile karşılaştırmaktır. Fakat bu çalışmanın en temel bulgusu Karadeniz bölgesindeki ülkelerin birbiriyle rekabet halinde olan farklı bölgeselcilik projeleri içerisinde yer almalarından dolayı, bu bölgede bölgeselcilik zayıf ve gelişmemiş durumdadır

Since the end of the Cold War, the study of regions has become a major preoccupation of political scientists. And yet, regionalism still means many different things to many different peoples in too many different contexts. Nonetheless, economic interdependences through trade and other intraregional activities is one of the main pillar of regionalization in any given example. The driving impulse of this paper is that there is a hypothetical relation with emerging regional economic relations and regionalism. That is, regionalism and emerging regional economic activities self-enforcing phenomena at least on theoretical front. In this sense, it is sensible to look at the some of the trade and economic statistics to determine the state of regionalization in the Black Sea. Therefore, this paper first tries to demarcate “Black Sea Region” and possible sub regions than will comparatively analyses the economic regionalization process by comparing some other regions and sub regions. The main finding of the paper suggests that fundamentally due to the fact that every member of Black Sea regions has been engaging with other exclusive regionalization movements, regionalization in the wider Black Sea is weak and underdeveloped
Karşılaştırmalı Bir Çerçeveden Ekonomik Bölgeselleşme ve Karadeniz
Keywords: Uluslararası İlişkiler; Siyasi Bilimler